2010
DOI: 10.1068/p6455
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Rotating Snakes’ in Smooth Motion do Not Appear to Rotate

Abstract: 'Rotating snakes' is an illusory figure in which the 'snakes' are perceived to rotate. We report that when the image moves smoothly, the snakes do not appear to rotate, although the retinal images are continuously refreshed. Therefore, to produce the illusion, the image should remain stationary (without being refreshed) for some time on the same retinal position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…By contrast, the streaming in the Enigma illusion did not apparently decrease, and the Ouchi illusion was even enhanced by adding smooth motion. The present results, showing differences in the time courses of perceived motion in the illusions, are consistent with the previous results (Billino et al, 2009;Tomimatsu et al, 2010).…”
Section: Ouchi and Enigma Illusionssupporting
confidence: 82%
“…By contrast, the streaming in the Enigma illusion did not apparently decrease, and the Ouchi illusion was even enhanced by adding smooth motion. The present results, showing differences in the time courses of perceived motion in the illusions, are consistent with the previous results (Billino et al, 2009;Tomimatsu et al, 2010).…”
Section: Ouchi and Enigma Illusionssupporting
confidence: 82%
“…In support of this idea, Backus and Oruç (2005) found that saccade-like jumps in the Rotating Snakes pattern produced illusory rotation, whereas small jitter of the image was ineffective. Similarly, Tomimatsu et al (2010) found that fast displacements of the image produced a strong illusory percept, whereas smooth motion resulted in a much weaker illusion.…”
Section: Role Of Fixation Instability In the Perception Of The Rotatimentioning
confidence: 99%
“…However, possibly due to peripheral viewing, the illusion was not seen. As a dotted line biases its perceived motion direction to the line orientation (Ito et al 2009), detected motion directions in the shorter sector conditions may be circular along the disk edge. On the other hand, if the longer sector is misperceived in motion direction by the aperture problem, the perceived motion direction would also be circular around the disk.…”
Section: Resultsmentioning
confidence: 99%
“…The Chopsticks illusion and the Rotating Rings illusion (Anstis 2003) change the perceptual property of the intersections, resulting in a failure to track the intersection visually, although induced motion did not affect the tracking motion in spite of the perceived distortion of the motion path (Anstis and Ito 2010). Conversely, Tomimatsu et al (2010) showed that smooth pursuit eye movement greatly reduces the effect of the Rotating Snakes illusion.…”
Section: Introductionmentioning
confidence: 99%